Production and quality of mango fruits cv. Tommy atkins fertigated with potassium in semi-arid region - Carneiro, Marcio Alves; Nascimento Lima, Augusto Miguel; Lucena Cavalcante, Italo Herbert; Melo de Sousa, Karla dos Santos; Alencar Oldoni, Fernando Campos [UNESP]; Barbosa, Karine da Silva (Soc Brasileira Fruticultura, 2018)
Correct management of potassium (K) fertilization is of fundamental importance for mango orchards, and K is one of the most exported and yield-limiting nutrients. Thus, an experiment was carried out to evaluate the production and physical-chemical characteristics of Tommy Atkins mango fruits under fertigation with different doses of potassium chloride and potassium sulfate in the semi-arid region. The experimental design was randomized blocks in split plots, using five K doses (50, 75, 100, 125 and 150% of the recommended dose) in the plots and two sources of K (potassium chloride - KCl and potassium sulfate - K2SO4) in the subplots, with four replicates. The following characteristics were evaluated: transverse and longitudinal diameters, skin thickness, fruit weight, production per plant, pulp percentage, hydrogen potential (pH), soluble solid (SS), ascorbic acid (VIT C), titratable acidity (TA) and SS/ TA ratio. The doses and sources of K applied through fertigation caused significant effect on fruit physical-chemical characteristics and production per plant in Tommy Atkins mango, particularly at the dose of 349 g plant(-1) of K2SO4, which led to higher production per plant and guaranteed the minimum quality required for fruit physical-chemical characteristics.
Keywords: Mangifera indica L.; soil fertility; physical-chemical characteristics